Sustainable Investment Planning Model on Suramadu Bridge Area for Smes Central Development In Surabaya and Madura - T Ade, Reswanda; Ikhsan Setiawan, Muhammad; Dhaniati, Iswachyu; ., Suhermin (International Journal of Engineering and Technology, 2019)
The paper evaluates practice which utilized pay-back, internal rate of return (IRR), and the net present value (NPV) of public partnership (PPP) projects in Indonesia. Both developed and developing countries experience an increasing of interest in the adoption of PPP policy by their governments after the global crises that occurred from 2007 to 2008. Then, the governments of most countries are now searching to tap the private sectorâ€™s expertise as well as the capital in order to reduce the deficit of infrastructure. In Indonesia, PPP supports the welfare and prosperity of local government and community as well. It is obvious that sustainable development is the need in procurement of government in its public facilities and technology development. Investment properties and property play significant and positive role in the performance of a business. The small business and Medium Enterprises in Suramadu Bridge area itself can accommodate more than 150 thousands of people in which the maximum of capacity of activities is more than 620 thousands of people. Besides, the width of tourism business zone inside the Bridge area is more than 20 hectares. For the trade business zone in Suramadu Bridge, the width is approximately more than 70 ha.Â In integrated area of small business and medium enterprises, it is recognized as the highest investment value among all. Meanwhile, the CBD investment area is recognized as the fastest payback period (PBP) in terms of its investment value. Â Â Â Â Â Â Â Â Â Â Â